Spain : Converging with the European Community - Pastor Campos, Gonzalo (Occasional Papers; Occasional Paper ;, 1993)
Spain's participation in European integration has strengthened its policymaking credibility and created an enviroment conducive to sustainable economic growth. Over the last decade, Spain has seen improvements in inflation, output, employment, and its balance of payments, and it has substantially reformed its product, labor, and financial markets. This paper reviews Spain's past economic performance and sees good prospects for further rises in living standards.